P76 The determinants of subjective wellbeing: an analysis of a health and wellbeing survey in southeast england. (2nd September 2017) - Lagnado, AM; Gilchrist, K; Memon, A
Abstract : Background: The concept of wellbeing is now increasingly used as one of the key measures of societal progress, along with the traditional methods that are based on economic activity. Subjective wellbeing (SWB) is a construct by which national wellbeing can be measured—this can inform development of health and social policy. The objective of this study was to determine the association between sociodemographic/personal factors and low subjective wellbeing. Methods: Data from the health and wellbeing survey conducted in Brighton and Hove in 2012 (n=2, 035) was analysed. The survey included the Office of National Statistics verified measure of SWB, which consisted of four questions regarding life satisfaction, fulfilment, happiness and anxiety. Low SWB was the outcome measure, the threshold of which was determined according to the Faculty of Public Health outcome framework. The survey also included a range of population measures, sixteen of which were chosen as explanatory variables. The analysis included descriptive statistics and multivariate logistic regression, using the SPSS statistical programme. Results: In the multivariate analysis, poor general health (self-reported) was strongly associated with low SWB [dissatisfaction with life (adjusted OR=3.9, 95% CI, 2.7–5.6); unfulfilled (3.4, 2.3–4.8); unhappiness (3.0, 2.1–4.2); anxiety (2.4, 1.7–3.3)]. Other factors found to be significantly associated with low SWB included: illness and disability, low social capital, lack of physical exercise, a history of self-harm, not owning a home, not being in a relationship and being middle aged. On the other hand, unemployment, deprivation and poor education were not associated with SWB. Conclusion: This study demonstrates that an individuals SWB is likely to be affected by a number of sociodemographic/personal factors. The limitations of this study include the extent of external validity, the lack of causality and potential selection and information bias. These findings are relevant to the design and delivery of policy aimed at improving the perception of wellbeing in individuals, and the general population.